Molecular spectroscopic behaviors of beta-arbutin in anti-skin cancer. Issue 3 (15th March 2020) - Su, Yanbin; Sun, Xuwei; Wu, Ruixue; Zhang, Xing; Tu, Yunzhou
Abstract: The purpose of this study was to explore the molecular spectroscopic behaviors of the beta-arbutin on the toxic aldehyde of trans-crotonaldehyde in anti-skin cancer. Results revealed that both hydroxymethyl and phenolic hydroxyl of beta-arbutin led to the shift of the maximum ultraviolet peak of trans-crotonaldehyde from a very significant absorption peak at 300 nm to a very weak absorption peak at 310 nm and the significant shift of the aldehyde Raman band at 1689/cm of the toxic trans-crotonaldehyde in mitochondria and aldehyde dehydrogenase, respectively. The beta-arbutin acting on the toxic trans-crotonaldehyde highlighted the potential of anti-skin cancer and provided a valuable clue for the new application of the beta-arbutin.